THE ROLE OF BANK DEPOSIT POLICY IN THE DEVELOPMENT OF BANK DEPOSIT OPERATIONS (European Journal of Economics, Finance and Business Development, 2025)
This article thoroughly investigates the role of bank deposit policy in resource mobilization. Specifically, the main directions of deposit policy in commercial banks, as well as the processes and principles of its formation, are examined in both theoretical and practical aspects. Additionally, proposals are presented to enhance the role of deposit policy in resource mobilization by commercial banks.